Potential of polymer as dopant in photocatalyst to boost degradation of pollutants: a mini review - Mahmuelee Torlaema, Tasnim Aisya; Jaafar, Nur Farhana; Abdul Mutalib, Aunie Afifah; Lahuri, Azizul Hakim; Wahyuni, Endang Tri (Institution of Chemical Engineers, 2024)
The field of photocatalysis has recently gained significant attention as a revolutionary technique, enabling sustainable chemical processes that utilize light energy to facilitate complex reactions. Photocatalysts have emerged as crucial components in various environmental and energy-related domains, showcasing their importance and impact. The present publication explores the synthesis techniques and benefits of polymer-based photocatalysts, specifically emphasizing their use in environmental remediation and energy production. The integration of polymers as dopants in photocatalysts is a promising approach to improve the breakdown of contaminants in environmental remediation procedures. This study seeks to comprehensively explore the area of polymer-based photocatalysts, which has attracted substantial attention in the field of photocatalysis for enabling sustainable chemical processes. More precisely, it investigates how well these photocatalysts can eliminate pollutants, with a focus on the deliberate addition of polymer using various methods to improve their effectiveness. Several synthesis approaches, such as thermal polymerization, biological template, microwave-assisted coordination, and one-step thermal copolymerization, are examined to determine their efficacy in creating photocatalysts based on polymers. Moreover, this manuscript extensively examines the benefits and impacts of polymers on photocatalysts, emphasizing their contribution to increase photocatalytic activity and offering improved stability and functionality. Polymer dopants significantly broaden the spectrum of light absorption wavelengths, and enhance the separation of charge carriers, thus enabling more efficient destruction of pollutants. By drawing upon influential contributions in the field, this discussion highlights the significant influence of polymer-doped photocatalysts in the domains of environmental remediation and energy generation. By integrating extensive research and forward-thinking, this article highlights both the existing advancements in the field and the potential for a future characterized by environmentally friendly and sustainable solutions.